Does religiosity influence ethical sensitivity? An investigation on Malaysian future accountants / Maisarah Mohamed Saat, Stacey Porter and Gordon Woodbine - Mohamed Saat, Maisarah; Porter, Stacey (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
This study examines factors influencing religiosity and investigates its effect on the ethical sensitivity of a sample of 378 Malaysian accounting students from five universities. Religiosity is represented by the twelve faith maturity items developed by Benson, Donahue and Erickson (1993). Sixteen ethical scenarios of various business issues devised by Longenecker, McKinney and Moore (1989) are used to assess ethical sensitivity. The findings of this study show that religious affiliation, religious education background and type of institution influence the types of religiosity, namely Vertical, Horizontal, Integrated faith and Undeveloped faith. Students affiliated with Islam and Hinduism are inclined to possess Vertical and Integrated faith religiosity. Students attending Islamic religious secondary school and a related Islamic university possess strong religious views and are inclined to have a close relationship with God (Vertical religiosity) or commit to both spiritual and societal relationships (Integrated faith). This study also found that religious affiliation, religious education background, type of institution and religiosity (faith maturity) affect students’ ethical sensitivity, but the impact is situational. Based on the results it is recommended that the Malaysian education process needs to emphasise not only intellectual ethical perspectives for students but also religious positions.